Coordinated multi-level model predictive control of energy in electric railway traction systems : doctoral thesis - Novak, Hrvoje (H. Novak ; Faculty of electrical engineering and computing, 2019)
Railway transport systems are complex technical systems that consume significant amounts of energy and are suitable for advanced energy management approaches to make them more proactive participants in the next generation electrical smart grids. A railway energy management system based on hierarchical coordination of traction substation energy flows and on-route trains energy consumption is proposed in the thesis. The railway system is divided into energy-efficient individual trains energy consumption management as lower level, and the price-efficient traction substation energy flows management as higher level. Lower, trains energy consumption level jointly optimizes the on-route energy consumption of each individual train while respecting the route constraints and timetables, while the higher, energy flows management level balances the energy flows between accelerating trains energy consumption, decelerating trains energy production, local energy storages and energy taken from the grid. The levels are then coordinated through parametric hierarchical model predictive control with the main goal of additionally increasing the energy efficiency and decreasing the operational costs of the overall system. Through interactions with the utility power grid on the higher level, the system is able to provide ancillary services and respond to various grid requests. At the same time, lower level trains driving profiles are adjusted to attain the minimal cost of system operation with timetables and on-route constraints respected. The approach of hierarchical decomposition and coordination is not only limited to railway systems but is suitable for application to many different complex systems such as buildings or water distribution systems, whose comprehensive consideration in a single control system makes it challenging for real-time implementation. The proposed methodology is validated with an extensive case study analysis. Validation environment and simulation scenarios are put together following the guidance of industry experts such that relevant phenomena are included and realistic system behaviour is achieved. Keywords: piecewise-affine train model; energy-efficient train traction control; energy storage systems; cost-efficient traction substation energy flows control; railway system energy management; multi-parametric model predictive control; critical regions; hierarchical coordination.